ORTHOPTERA DIVERSITY OF BHARATHAPUZHA RIPARIAN ECOSYSTEM, PALAKKAD DISTRICT, KERALA - AKSHAD, M. ALI (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
Orthoptera diversity of Bharathapuzha riparian ecosystem was conducted from April 2019 to January 2020. Maximum species abundance was recorded in Monsoon season 21 species (Karakkad), 21 species (Mannanur) and 16 species (Thrangali) were obtained. Similarly followed by pre- monsoon 15 species (Karrakkad), 11 species (Mannanur) and 9 species (Thrangali) and followed by Post- monsoon 8 species (Karakkad), 8 species (Mannanur) and 10 species (Thrangali) respectively.